Friction and Wear Performance Evaluation of Bio-Lubricants and DLC Coatings on Cam/Tappet Interface of Internal Combustion Engines - Zahid, Rehan; Bhutta, Muhammad Usman; Mufti, Riaz Ahmad; Abdullah, Muhammad Usman; Masjuki, Haji Hassan; Varman, Mahendra; Kalam, Muhammad Abul; Ali, Mian Ashfaq; Aslam, Jawad; Akhtar, Khalid (MDPI, 2021)
: The environmental concerns associated with artificially formulated engine oils have forced a shift towards bio-based lubricants. The deposition of hard coatings on engine components and migrating to environmentally friendly green lubricants can help in this regard. Chemically modified forms of vegetable oils, with better low-temperature characteristics and enhanced thermo-oxidative stability, are suitable substitutes to conventional lubricant base oils. The research presented in this manuscript was undertaken to experimentally investigate the wear and friction performance of a possible future generation of an environmentally friendly bio-based lubricant as a potential replacement for conventional engine lubricants. In order to quantify the tribological benefits which can be gained by the deposition of DLC coatings, (an (a-C:H) hydrogenated DLC coating and an (a-C:H:W) tungsten-doped DLC coating) were applied on the cam/tappet interface of a direct acting valve train assembly of an internal combustion engine. The tribological correlation between DLC-coated engine components, lubricant base oils and lubricant additives have been thoroughly investigated in this study using actual engine operating conditions. Two additive-free base oils (polyalphaolefines (PAO) and chemically-modified palm oil (TMP)) and two multi-additive-containing lubricants were used in this investigation. Real-time drive torque was measured to determine the friction force, detailed post-test analysis was performed, which involved the use of a specialized jig to measure camlobe wear. An optical profilometer was used to measure the wear on the tappet, high-resolution scanning electron microscopy was employed to study the wear mechanism and energy-dispersive X-ray spectroscopy was performed on the tested samples to qualitatively access the degradation of the coating. When using additive-free TMP, a low friction coefficient was observed for the cam/tappet interface. The presence of additives further improved the friction characteristics of TMP, resulting in reduced average friction torque values. A tremendous enhancement in wear performance was recorded with a-C:H-coated parts and the coating was able to withstand the test conditions with little or no delamination.